Republic of Congo : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This paper assesses the Republic of Congo's discussions in 2013 Article IV Consultation. Though having abundance of natural resources, notably oil and iron ore, Congo has achieved limited progress in poverty alleviation, and remains vulnerable to external shocks. Weak governance and business conditions are significant constraints to private sector development and growth inclusiveness. The IMF report shows that Congo's main challenge is to ensure long-term macroeconomic stability in the face of oil revenue volatility and exhaustibility, and to make growth more inclusive.